2022
DOI: 10.1002/bio.4365
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photometric properties of efficient white‐emitting phosphor of M‐AMG transition metal complexes for OLED applications

Abstract: Progression in lighting sources mainly depended on new, robust energy‐efficient diodes due to their advanced photometric properties. All organic light‐emitting sources are constant energy‐efficient devices and will be the light of the future. We explore the potential of transition metal complexes by focusing on cobalt(II), nickel(II), and copper (II) with aminoguanidine naphthoate as white phosphors in organic light‐emitting diodes (OLEDs). The phosphors synthesized at optimized temperature were characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The results of this study indicated indirect damage to cell organelles apart from the sites of photosensitizer localization and led to cell death in PDT. Swathika and Natarajan [55] synthesized complexes of (Ni[2NA‐AMG‐2H 2 O]), (Co[2NA‐AMG‐2H 2 O]), and (Cu[2NA‐AMG‐2H 2 O]) for developing white phosphors. The results of this study suggested that Cu(2NA‐AMG‐2H 2 O) had outstanding optical properties with a high colouring index, which opened a new avenue for light sources.…”
Section: Overview Of Published Researchmentioning
confidence: 99%
“…The results of this study indicated indirect damage to cell organelles apart from the sites of photosensitizer localization and led to cell death in PDT. Swathika and Natarajan [55] synthesized complexes of (Ni[2NA‐AMG‐2H 2 O]), (Co[2NA‐AMG‐2H 2 O]), and (Cu[2NA‐AMG‐2H 2 O]) for developing white phosphors. The results of this study suggested that Cu(2NA‐AMG‐2H 2 O) had outstanding optical properties with a high colouring index, which opened a new avenue for light sources.…”
Section: Overview Of Published Researchmentioning
confidence: 99%
“…Consequently, scientists have been motivated to explore alternative candidates. Meanwhile, transition metal complexes, known for their high specific surface area, adjustable pore size and good thermal stability, have found extensive application prospects in magnetism, [29][30][31][32][33] catalysis, [34][35][36] luminescence, 34,37,38 electrochemical sensors, [39][40][41] etc. As a result, an encouraging strategy of incorporating POMs into transition metal complexes (TMCs) to build POM-based transition metal complexes (POM-TMCs) was put forward.…”
Section: Introductionmentioning
confidence: 99%